Analyser les textes avec internet : étude d’une pratique professionnelle en transformation - Magali Brunel; Laurent Heiser (Recherches en Éducation)
The use of the Internet in the classroom is a topical issue within the school. Through a case study, we analyze a device that allows students to tap into available online resources to study literary texts. This is based both on the use of digital technology in the classroom and on a practice of text analysis based on students' research and proposals rather than on the teacher's choices. We analyse how the implementation of this system accentuates some of the teacher's concerns and, by studying two interviews conducted at the beginning and end of the experiment, we seek to identify some signs of appropriation. The analysis establishes that the process is based in particular on the way in which the teacher manages to relate his habits to the technical and didactic constraints induced by the system but also to the actual heterogeneous digital media practices of the pupils. This case tends to illustrate that the introduction of a digital learning system requires a long period of appropriation and highlights the need for explicit instruction in digital media literacy skills based on taking into account students' informal practices in the classroom.